Audiobooks on Compact Discs in Lithuania - Gudinavičius, Arūnas; Naktinytė, Laima (Knygotyra, 2011)
The object of the article is audiobooks on compact disks that have been published in Lithuania in 2000–2009. The aim of the work was to explore the publishing scope of audiobooks on CDs in Lithuania and the repertoire of these books.After analysing theoretical materials, the conception of an audiobook has been formulated and the main classification criteria have been distinguished. Audiobooks on CDs that have been published in Lithuania in 2000–2009 have been analysed in different aspects. The analysis of statistical data and repertoire of audiobooks enabled to determine the current situation of their publishing and to estimate perspectives for the future. The conclusion is that audiobooks are not very common and not very widely used in Lithuania. These are the reasons why the scope of publishing this kind of books is not large. The biggest part of their repertoire is audiobooks for children and for language learning.
Keywords: audiobook; compact disc; publishing